Conceptions of Integral Education in contemporary Brazilian context - Miguel, Priscila Caroline [UNESP]; Conceicao, Aline de Novaes [UNESP]; Pereira, Adriana Alonso [UNESP] (Univ Federal Norte Tocantins-ufnt, 2024)
It is important to work with Integral Education, an education whose advocacy is constant and acceptable in various spheres. However, confusion between Integral Education and terms such as full-time schools, full day schooling and full-time is still common. Between the 1930s and 1970s in Brazil, the concept of Integral Education involved physical, intellectual, social, and civic elements, as Concei & ccedil;& atilde;o (2022) states. However, what are the current conceptions of Integral Education? Thus, the the purpose of this article is to identify and analyze the conceptions of Integral Education in contemporary Brazil. To this end, a systematic configurative literature review was conducted, based on consultations in Scielo, Oasisbr, Eric, and Doaj, with the descriptor Integral Education and selecting texts in Portuguese that contained these words in their titles and were published from 2018 to the first semester of 2024, respectively the year in which the National Common Curricular Base was approved and the year and semester in which the research was developed. It was found that, in contemporary times, the conceptions of Integral Education involve the following elements: intellectual/cognitive, physical/motor, affective, ethical, social, symbolic, cultural, musical, scientific, environmental, moral, artistic, emotional, philosophical, biological, political, recreational/playful, technological, and creative.
Keywords: integral education; conceptions of integral education; comprehensive education